Penilaian Tingkat Transparansi dalam Proses Penyusunan RTRW Kota Bandung - Denny Zulkaidi; Nasrina Kumala Sari (Journal of Regional and City Planning, 2004)
The preparation and publication of Spatial Plan of Bandung city 2010 has been formally finished in February 2003. However, there is a doubt in the public's eye as to whether or not this spatial plan had been formulated in a transparent manner. Considering that transparency as a significant principle in good governance is important in the spatial planning process, the level of transparency in the planning process of the Spatial Plan of Bandung City should be assessed. Based on specific criteria and indicators formulated from spatial planning related regulations, the assesment come to a conclusion that the planning process of the Spatial Plan of Bandung City did not fully comply the principle of transparency. The shortcomings particularly were in the forms of information and variation of information media